2012
DOI: 10.1073/pnas.1119396109
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to anticancer drugs can result in transgenerational genomic instability in mice

Abstract: The genetic effects of human exposure to anticancer drugs remain poorly understood. To establish whether exposure to anticancer drugs can result not only in mutation induction in the germ line of treated animals, but also in altered mutation rates in their offspring, we evaluated mutation rates in the offspring of male mice treated with three commonly used chemotherapeutic agents: cyclophosphamide, mitomycin C, and procarbazine. The doses of paternal exposure were approximately equivalent to those used clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 25 publications
3
55
0
1
Order By: Relevance
“…Results consistent with the above were obtained also in further X-ray investigations by Barber et al [ 49] and Abouzeid Ali et al [ 22], as well as generally similar results being obtained for other DNA-damaging agents (namely, ENU [48] and three chemotherapeutic drugs [24]). Following 1 Gy of X-rays in utero at 12 days of gestation and mating at 8 weeks of age, raised ESTR mutation frequencies were observed in the germline and somatic cells of the first-generation (F 1 ) offspring after paternal (F 0 ) in utero irradiation, but not after maternal in utero irradiation [49].…”
Section: Evidence Indicative Of Transgenerational Effects In Expersupporting
confidence: 86%
See 2 more Smart Citations
“…Results consistent with the above were obtained also in further X-ray investigations by Barber et al [ 49] and Abouzeid Ali et al [ 22], as well as generally similar results being obtained for other DNA-damaging agents (namely, ENU [48] and three chemotherapeutic drugs [24]). Following 1 Gy of X-rays in utero at 12 days of gestation and mating at 8 weeks of age, raised ESTR mutation frequencies were observed in the germline and somatic cells of the first-generation (F 1 ) offspring after paternal (F 0 ) in utero irradiation, but not after maternal in utero irradiation [49].…”
Section: Evidence Indicative Of Transgenerational Effects In Expersupporting
confidence: 86%
“…From the very high frequencies of induction it was concluded that mutations arise from some form of radiation-induced instability leading to non-targeted events in the irradiated germline. More recent studies, entirely from the Dubrova group, using pedigree analysis and/or SM-PCR analysis of the F 0 sperm, have confirmed and extended these results to a variety of additional biological and exposure conditions (including ENU exposure [48], in utero irradiation [49],, chemotherapeutic drug exposures [24, 50] and lower- dose and chronic irradiation [23]), and to ESTR mutations in somatic cells of the irradiated (F 0 ) mice [49]. Results from all of the above showed high-frequency induction of ESTR mutations in the directly-irradiated germline or somatic tissues.…”
Section: Evidence Indicative Of Transgenerational Effects In Expermentioning
confidence: 91%
See 1 more Smart Citation
“…It has therefore been hypothesised that radiation-induced complex double-strand DNA breaks may represent such triggering events [96]. To establish whether GI is attributed to the induction of a specific subset of DNA lesions, studies by Dubrova et al have analysed the transgenerational effects of paternal treatment by a number of mutagens, exposure to which mostly causes alkylation of DNA and other types of DNA damage [97, 98]. The results of these studies clearly show that paternal exposure to the alkylating agent ethylnitrosourea, as well as to three anticancer drugs cyclophosphamide, mitomycin C and procarbazine can destabilise the offspringā€™s genome in a similar manner to that following paternal irradiation.…”
Section: Types Of Non-targeted Effectmentioning
confidence: 99%
“…Barber et al, 2002; R. C. Barber et al, 2006; Dubrova, 2003; Dubrova et al, 2008; Glen et al, 2012). Thus, these data suggest that smoke exposure might induce lasting genetic and epigenetic changes that could impact subsequent unexposed generations.…”
Section: Introductionmentioning
confidence: 99%